The Penerapan Model Pembelajaran Flipped Classroom Pada Mata Pelajaran Pai Terhadap Motivasi Belajar - Safitri, Tami Safitri; Romli, Romli; Irawan, Dody (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
This study aims to determine the application of the learning model flipped classroom on PAI subjects on student learning motivation and to find out the application of the flipped classroom learning model to students' learning motivation through quasi-experimental studies on PAI subjects Class X Office Governance Automation at SMK Yapensu Sungailiat. This study uses a quasi-experimental type of research with qualitative approach. This study uses experimental class subjects, namely the students of class X Office Management Automation at SMK Yapensu Rivers. Field data collected through observation, structured interviews and documentation. Data were analyzed using data reduction, display data and data verification. Furthermore, the presentation of data using narrative techniques namely using data as an explanatory theory, using theory the concept of flipped classroom learning Bergman, J & A. Sams (2012), strategy learning flipped classroom Graham Brent Johnson (2013), and flipped classroom with bloom taxonomy Mustafa Cevikbas and Ziya Argun (2017). The results of this study are an increase in students' learning motivation after the implementation of the flipped classroom learning model in the process learning. Vary the flipped classroom learning model with learning methods, such as the lecture method, question and answer, demonstration, problem based learning and gamification can develop student attitudes in critical thinking, active, creative, interactive, responsive and collaborative. The use of learning media in the form of learning videos, e-books and e-books the power point given by the researcher before the implementation of learning in class can increase students' independence in learning. This study agrees with Anis Umi Khoritunnisa (2020), Wolfaharda Fitriani Sinmas, Chandra Sundaygara and Kurriawan Budi Pranata (2019), Nadya Treesna Wulansari (2018), Prima Vidya Asteria (2021) who stated that the application of the flipped classroom learning model in the learning process can make students think critically, active, creative, collaborative, interactive and can increase student learning motivation. While this research differs in opinion from the research conducted by Esa Gumelar (2019) which states that the flipped classroom upside down is not an absolute factor to affect independence student learning. However, there are other factors that affect learning independence one of the students' ability to understand the learning material.